Small ruminant production systems in Africa - Wilson, R.T. (OAU/STRC, 1986)
Outlines the importance of small ruminants in Africa, describing the production systems in the different ecological zones in relation to traditional and modern methods of production. Provides information on general management practices and on ownership patterns and flock structures in relation to the goals and objectives of the producers.